CLINICO-STATISTICAL STUDY ON EDENTULOUS SPACES EVOLUTION IN DRUG CONSUMING PATIENTS - Adriana Bisoc; Mihaela Păuna; Livia Alice Tănăsescu; Oana Cella Andrei (Romanian Society of Oral Rehabilitation, 2019)
Drug consuming patients are cases that require a specific approach in prosthetic treatment, due to the high susceptibility to dental affections and, therefore, the increased risk of losing their teeth. Aim: to determine a correlation between the number of edentulous spaces and the drug-consuming patients' compliance to dental treatment. Material and method: 35 drug consuming patients were treated for two and a half years. The degree in following the agreed treatment plan and in respecting the hygiene instructions was registered. The recorded data was analyzed using statistical methods (SPSS, Student's T test, ANOVA), corresponding to each category - uniformly distributed data versus data that procures statistical variations. Using T test, the hypothesis that the number of edentulous spaces is not significantly influenced by the time span of using drugs was tested. Results: The bivariate correlation between the number of edentulous spaces and the time span of using drugs (months) resulted in a Pearson correlation coefficient of 0.446 (positive, middle) and a statistical probability p-stat=0.007. Between the two factors there is a moderate positive and statistically significant linear correlation. The type of drug used does not determine significant differences regarding the number of edentulous spaces (P 0.140). The bivariate correlation between the number of edentulous spaces and the time passed from the last appointment showed that they are weak positive and not statistically significant correlated. Applying the regression model, only 9% of the variation of the number of edentulous spaces appeared in time. F-stat value was 3.2 and p-stat was >0.05, which certifies the fact that the time passed from the last appointment is not significantly influencing the number of edentulous spaces. Conclusions: This clinico-statistical study demonstrated the cause-effect relationship between the consumption of drugs and oro-dental changes (edentulous spaces). This data is useful in elaborating, accepting and executing a treatment plan.